The extended law of corresponding states when attractions meet repulsions. Issue 19 (20th March 2018) - van Gruijthuijsen, K.; Obiols-Rabasa, M.; Schurtenberger, P.; Bouwman, W. G.; Stradner, A.
Abstract : Rescaling of the phase diagram via B 2 * (Baxter stickiness) and the interaction potential for short-range attractive colloids with shorter- and longer-ranged repulsions. Abstract : Short-range attractive colloids show well-defined phase behaviour in the absence of repulsions, and highly intriguing equilibrium gelation in the presence of long-range repulsions. We present the state diagram of short-range attractive colloids with repulsions that range from fully screened to intermediately ranged, i.e. longer-ranged than the attractions, but shorter ranged than the colloid size. We demonstrate that although the macroscopic phase behaviour does not change perceptibly, there is a dramatic increase of inhomogeneities once the repulsions become longer-ranged than the attractions. The interaction potentials are characterized with small angle neutron scattering, and used to renormalize the state diagram with the minimum in the interaction potential, min[ U ( r )], and with the reduced second virial coefficient, B 2 *. We find that the extended law of corresponding states captures the onset of phase separation for shorter ranged repulsions, but fails for longer ranged repulsions. Instead, for a given model of U ( r ), the transition from visually homogeneous fluid to phase separation and/or gelation can be rescaled with min[ U ( r )] over the full range of repulsions. Finally, we suggest a generic state diagram to describe the effect of repulsions on short-range attractive systems.